Discontinuing early prophylaxis in severe haemophilia leads to deterioration of joint status despite low bleeding rates - Nijdam, Annelies; Foppen, Wouter; Kleijn, Piet de; Mauser-Bunschoten, Evelien P.; Roosendaal, Goris; van Galen, Karin P. M.; Schutgens, Roger E. G.; van der Schouw, Yvonne T.; Fischer, Kathelijn (Thrombosis and Haemostasis, 2016)
Prophylaxis is the recommended treatment for children with severe haemophilia A, but whether prophylaxis should be continued in adulthood is still under debate. Previous studies with limited follow-up have suggested that some patients may be able to stop prophylaxis in adulthood, while maintaining good joint health. This single-centre observational cohort study examined patients with severe haemophilia A born 1970–1988 without inhibitor development, and assessed the long-term consequences of discontinuing prophylaxis. Patient-initiated changes in prophylaxis, including all switches to on-demand treatment lasting a minimum of two consecutive weeks, were recorded from the time self-infusion began until the last evaluation. Sixty-six patients were evaluated at a median age of 32.4 years: 26 of patients had stopped prophylaxis for a median of 10 years, 15 had interrupted prophylaxis and 59 had continued prophylaxis. Annual joint bleeding rate (AJBR), Haemophilia Joint Health Score (HJHS-2.1; 0–124 points), radiological Pettersson score (0–78 points) and Haemophilia Activities List score (HAL; 100–0 points) were compared between patients who stopped and patients who continued prophylaxis. Although self-reported bleeding rates and functional limitations were similar in both groups (AJBR: 1.5 vs 1.2 and HAL: 84 vs 84 for those who stopped and continued prophylaxis, respectively), objective assessment of joint status showed increased arthropathy after 10 years of on-demand treatment in patients who stopped prophylaxis compared with those who continued (HJHS: 23 vs. 14 and Pettersson: 16 vs 5, respectively; P< 0.01). These results support continuation of long-term prophylaxis in adults and demonstrate the need for objective monitoring of joint status.Trial registration: Dutch Trial Registry number 3098; UTN U1111–1121–7069.
Keywords: Arthropathy; joint bleed; haemophilia; prophylaxis; X-rays